2019
DOI: 10.1515/reveh-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of water, sanitation and hygiene in HCFs: which tool to follow?

Abstract: Water, sanitation and hygiene (WASH) is important to improve and maintain the quality of health care services. Improving and managing WASH services require strong and consistent monitoring mechanisms to measure progress and direct efforts where needs are greatest. Although several tools are available to assess WASH in health care facilities (HCFs), there is always a dilemma among the program managers to select an appropriate tool for the assessment of WASH. Thus, it was aimed to perform a descriptive review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In our current COVID-19 climate, speed and efficiency are key design drivers-but the safety of patients and staff is also of paramount importance. Clean water, sanitation, and hygiene (WASH) programs are one of the ways to ensure such safety, and an investment in water and sanitation systems, is one of the most cost-effective pandemic preparedness strategies, especially in resource-constrained settings [13]. In health care facilities (HCFs), WASH is characterized as infrastructure, services, and behaviors that encompass water supply and water quality, sanitation facilities (including bathing or shower areas), soap and hand wash water availability, and certain elements of waste management in health care (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our current COVID-19 climate, speed and efficiency are key design drivers-but the safety of patients and staff is also of paramount importance. Clean water, sanitation, and hygiene (WASH) programs are one of the ways to ensure such safety, and an investment in water and sanitation systems, is one of the most cost-effective pandemic preparedness strategies, especially in resource-constrained settings [13]. In health care facilities (HCFs), WASH is characterized as infrastructure, services, and behaviors that encompass water supply and water quality, sanitation facilities (including bathing or shower areas), soap and hand wash water availability, and certain elements of waste management in health care (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2019 global report of WASH in HCFs, one in four HCFs lacked basic water services, one in five did not have sanitation services, and one in six had no hygiene services [15]. In the local context, water coverage in such facilities is 32% and the sanitation coverage is 85% while the hygiene data are not available [13]. Quality WASH facilities act as barricades to the transmission of the COVID-19 virus in health care facilities [16].…”
Section: Introductionmentioning
confidence: 99%
“…The cut-off points remain flexible and may be modified depending on the aim and purpose of WASH FIT users. While WASH FIT may not be a comprehensive tool [ 25 ], the potential utility and application of WASH FIT have been well-documented [ 20 , 26 , 27 , 28 ]. Moreover, WASH FIT will be further updated to accommodate additional topics, such as climate, occupational health, and gender [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are existing monitoring tools which can be useful in monitoring WaSH in HCF indicators. Patel et al [ 49 ] review on WaSH in healthcare monitoring tool developed from 1991 to July 2018 recommended the need for more comprehensive and concrete WaSH in health care monitoring tools. A recent assessment by the USAID and Maternal Child Survival Program on the Kenyan Health Management Information Systems (HMIS) indicated that half of hospitals surveyed used an electronic medical record that was not linked to the District Health Information Software (DHIS2) in 2016 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%